The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4067/s0301-732x2016000200017
|View full text |Cite
|
Sign up to set email alerts
|

Flea and ticks species from dogs in urban and rural areas in four districts in Chile

Abstract: Flea and ticks species from dogs in urban and rural areas in four districts in ChilePulgas y garrapatas en perros urbanos y rurales en cuatro regiones en Chile ABSTRACT. Fleas and ticks frequently parasitise canines worldwide and their prevalence in dogs is influenced by many factors including climate and geography, among others. Different studies worldwide have shown no clear pattern of an urban or rural preference by different species of fleas and ticks infesting dogs. The aim of this study is to identify sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
0
18
0
3
Order By: Relevance
“…Ctenocephalides felis, in particular, is considered a well stablished intermediated host [95][96][97]. The globally distributed C. felis is also a common parasite of dogs in the Metropolitan Region of Chile [13,64] although they were found at low prevalence on the dogs included in this study and lice were not found at all (data not shown).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Ctenocephalides felis, in particular, is considered a well stablished intermediated host [95][96][97]. The globally distributed C. felis is also a common parasite of dogs in the Metropolitan Region of Chile [13,64] although they were found at low prevalence on the dogs included in this study and lice were not found at all (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…In this sense, higher rates of exposure or infection were found in rural dogs when compared with their urban counterparts [61][62][63]. In the Metropolitan Region of Chile, the prevalence of R. sanguineus and Ctenocephalides canis was indeed higher in rural than in urban dogs [64].…”
Section: Discussionmentioning
confidence: 88%
“…Some of these mestizo dogs had been rescued directly from the street or living in shelters. This is important considering that A. reconditum is transmitted by vectors such as fleas (Ctenocephalides felis) and lice (Heterodoxus spiniger) [3] that commonly infest stray or refuged dogs rather than "pure" breed dogs [41,46]. In fact, a study in Zambia, reported a prevalence of 7.6% microfilariasis (different from D. immitis) in mestizo dogs and not any dog of "pure" breed with these nematodes among 272 dogs studied [47].…”
Section: Discussionmentioning
confidence: 99%
“…Los géneros y especies de garrapatas presentes en esta investigación han sido previamente identificadas en Yucatán, México (16)(17)(18)(19)26 (28). Por su parte, el género Ixodes infesta habitualmente animales en contacto con ambientes silvestres o peri-domésticos (29) e identificarlo en perros de comunidades rurales en Yucatán, se debe principalmente a que algunas veces son utilizados en actividades como la cacería de subsistencia (27).…”
Section: Discussionunclassified